(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Navigating complex healthcare cases demands a collaborative approach, with social workers and nurses as key partners. This article examines their joint efforts in addressing intricate scenarios to ensure comprehensive patient care. It outlines the distinct roles of social workers and nurses, emphasizing their expertise in psychosocial assessment and clinical management, respectively. Effective strategies for collaboration, including clear communication and interdisciplinary teamwork, are highlighted. Real-world examples illustrate successful collaboration in managing diverse patient needs. Challenges such as role ambiguity and organizational barriers are discussed, along with solutions to promote collaboration. Ultimately, this article underscores the critical role of social work-nursing collaboration in navigating complexity and enhancing patient outcomes.